SECURE STORAGE FOR SMART EDUCATIONAL INSTITUTION USING BLOCKCHAIN TECHNOLOGY - D. Sophia Navis Mary, Dr. S. Gopinathan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Educational institutions have seen significant growth over the years, the use of innovative new pedagogy, secure storage, and global access of documents is important and on-demand in today's blended learning environment. Blockchain has created a huge potential in several industries by providing seamless, time-efficient, and secure transactions. In this paper, we propose a blockchain-based smart storage system to manage student’s certificates, e-resources, academic credentials, and achievements rendering secure global access. The files are stored using the Proof of Work (POW) concept of Blockchain and access rights are defined using smart contracts. Also, this paper suggests how a public blockchain can be utilized to connect all the educational institutions under a university to provide global access, storage of educational records.